CLEAR cluster-catching for loop emendation and recovery - Melchor, Kyle Christopher L.; Pedrasa, Jhoanna Rhodette I. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Wireless Sensor Networks (WSNs) are becoming an integral part of monitoring and control systems. This is due to recent and great advancements in digital technology, communications and micro-electro-mechanical systems (MEMS). Low-Power and Lossy Network (LLN) devices are WSN devices that are resource-constrained when it comes to energy, memory and processing capabilities. The IETF has developed the Routing Protocol for Low-Power and Lossy Networks (RPL) to become the de facto standard in LLN routing. However, there are still a lot of documented issues with RPL and one of these is loops. Loops occur when a sub-DODAG loses a path to the Root and one of the nodes, which was a part of the critical path, suddenly resets its Rank and connects to its child. A possible solution to this problem would be to use Clustering, a technique that may possibly prevent loops due to its hierarchical nature and its efficiency in managing sub-networks. This work proposes to introduce clustering through the development of a scheme called Cluster-Caching for Loop Emendation and Recovery (CLEAR) which will be incorporated via a few additions to the current RFC for RPL (RFC 6550). Our results and analysis show that our implementation of CLEAR prevents the formation of loops and improves the over-all performance of disconnected sub-DODAGs with minimal changes to the existing RFC.
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman
Keywords: Routing protocols (Computer network protocols).; Hierarchical clustering (Cluster analysis).